Effects of low carbon supply chain practices on environmental sustainability: An empirical study on Indian manufacturing firms. (4th March 2019) - Das, Chiranjit; Jharkharia, Sanjay
Abstract : Purpose: The purpose of this paper is to empirically examine the relationships between low carbon supply chain practices and their relationships with environmental sustainability (ES) and the economic performances (EP) of firms. The study also includes an examination of the low carbon supply chain practices that are utilized by Indian manufacturing firms. Design/methodology/approach: Through a questionnaire-based survey, the data received from 83 Indian manufacturing firms was analyzed using a variance-based structural equation modeling technique to test the proposed hypotheses. Findings: The study indicates that carbon governance is a strategic imperative for the adoption of low carbon supply chain practices. Similarly, low carbon product and process design (LCPPD), manufacturing and logistics lead to improved ES. In addition, low carbon purchasing is positively related to the adoption of LCPPD, manufacturing and logistics. No significant relationship was found between the adoption of low carbon supply chain practices and the EP of a firm. Practical implications: The findings of this study may assist manufacturing managers in prioritizing operational practices for the reduction of emissions. Originality/value: This study provides two major contributions to green supply chain management. First, it provides comprehensive empirical evidence on low carbon supply chain practices that are being followed by Indian manufacturing firms. Second, this study also empirically validated a structural model of low carbon supply chain practices.